2012
DOI: 10.1021/jp3075767
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a High Work Function Solution Processed Vanadium Oxide Hole-Extracting Layer for Small Molecule and Polymer Organic Photovoltaic Cells

Abstract: We report a method of fabricating a high work function, solution processable vanadium oxide (V2O x(sol)) hole-extracting layer. The atmospheric processing conditions of film preparation have a critical influence on the electronic structure and stoichiometry of the V2O x(sol), with a direct impact on organic photovoltaic (OPV) cell performance. Combined Kelvin probe (KP) and ultraviolet photoemission spectroscopy (UPS) measurements reveal a high work function, n-type character for the thin films, analogous to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
61
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 54 publications
(120 reference statements)
4
61
1
Order By: Relevance
“…According to literature [25,26], MoO 3 is considered as a direct bandgap material and n is set as 0.5. V 2 O 5 -MoO 3 [27] and V 2 O 5 [28] are both reported as indirect bandgap materials and n shall be set as 2. In this study, we set n of MoO x and V 0.05 MoO x as 0.5, because of low doping concentration of V. For V 0.2 MoO x , V 0.5 MoO x and VO x samples, we set n = 2 for Tauc plot.…”
Section: Resultsmentioning
confidence: 99%
“…According to literature [25,26], MoO 3 is considered as a direct bandgap material and n is set as 0.5. V 2 O 5 -MoO 3 [27] and V 2 O 5 [28] are both reported as indirect bandgap materials and n shall be set as 2. In this study, we set n of MoO x and V 0.05 MoO x as 0.5, because of low doping concentration of V. For V 0.2 MoO x , V 0.5 MoO x and VO x samples, we set n = 2 for Tauc plot.…”
Section: Resultsmentioning
confidence: 99%
“…A VO x layer was formed below the Au S/D electrodes because the field-induced current in OFETs mainly flows within a few monolayers of the pentacene molecules. X-ray photoelectron spectroscopy (XPS) data from previous reports [15,16] showed that both thermal evaporation of vanadium oxide and the hydrolysis of vanadium precursor are likely to form vanadium sub-oxide (VO x ) instead of vanadium pentoxide (V 2 O 5 ) due to oxygen vacancies. The formation of VO x with solution-process was verified by comparing the UVeVis absorption spectrum with that of the thermally evaporated VO x film, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Such is the case of NiO, 9 MoO 3 , 10,11 CuO, 12 or V 2 O 5 . 13,14 For V 2 O 5 , one of its most widespread fabrication methods is the application of sol-gels made from vanadium (V) oxitriisopropoxide (V 2 O 5 -i) [14][15][16][17][18] or (NH 4 ) 3 VO 4 . 19,20,25 These precursors when used for the fabrication of flexible organic solar cells must be annealed at temperatures not exceeding 150…”
mentioning
confidence: 99%
“…We developed in-house software to control 21 As already mentioned, the applied fabrication methods are those obtained from sol-gels made from vanadium (V) oxytriisopropoxide (ViPr) or (NH 4 ) 3 VO 4 , among others. [14][15][16][17][18][19][20] In these cases, the precursor materials are selected for the fabrication of flexible solar cells where the sintering temperatures cannot exceed 150…”
mentioning
confidence: 99%